Legal Protection for Consumers in Online Transactions in Indonesia - Samsidar Samsidar (PT. Anagata Sembagi Education, 2024)
The development of information technology has changed the way people conduct transactions, especially in electronic commerce (e-commerce). Although online transactions provide convenience, various legal issues arise related to consumer protection, such as fraud, nonconforming goods, and difficulties in returning goods. This study aims to analyze legal protection for consumers in online transactions in Indonesia based on applicable laws and regulations, as well as to identify the challenges faced and solutions that can be applied. The research method used is qualitative with a normative legal approach. The results of the study show that although there are several regulations such as the Consumer Protection Law and the ITE Law, implementation in the field is still weak, especially in terms of law enforcement and consumer awareness. Synergy is needed between the government, business actors, and consumers to create a safe and fair ecommerce ecosystem. This article recommends improving regulations and increasing legal education and literacy for the community.